2014
DOI: 10.1007/s11746-014-2535-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Compositional Diversity of Fatty Acid Methyl Esters Profile in Nigella sativa L. Germplasm

Abstract: Nigella sativa L. is an annual underutilized crop of enormous significance, it contains more than 100 bioactive constituents having both pharmaceutical and industrial applications. Nigella sativa L. germplasm consisting of 32 genotypes was quantified for palmitic acid, stearic acid, oleic acid, linoleic and linolenic acid and results obtained varied in percentage. Lipid extracted by chloroform methanol 2:1 (24–37 %) was higher compared to n‐hexane (18–35 %) and chloroform methanol 1:3 (18–34 %). Extraction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Similar differences are seen in other major fatty acids, oleic and palmitic acids. It has earlier been reported that oleic acid ranges from 12.7% (Hamrouni-Sellami et al, 2008) to 27.4% (Iqbal et al, 2014), and palmitic acid ranges from 9.9% (Nickavar et al, 2003) to 18.4% (Cheikh-Rouhou et al, 2007). This variation was due to the climatic conditions of the study areas and the genetic structure of the plant.…”
Section: Change Of Fatty Acidsmentioning
confidence: 99%
“…Similar differences are seen in other major fatty acids, oleic and palmitic acids. It has earlier been reported that oleic acid ranges from 12.7% (Hamrouni-Sellami et al, 2008) to 27.4% (Iqbal et al, 2014), and palmitic acid ranges from 9.9% (Nickavar et al, 2003) to 18.4% (Cheikh-Rouhou et al, 2007). This variation was due to the climatic conditions of the study areas and the genetic structure of the plant.…”
Section: Change Of Fatty Acidsmentioning
confidence: 99%
“…It is also used as food additive, an ingredient and supplementary food etc. Generally seeds have been serving as food preservative and spice (Iqbal et al 2014). It is unique underutilized crop having potential both for agriculturally important traits and industry.…”
Section: Introductionmentioning
confidence: 99%
“…It increases body tone, stimulates menstrual periods and increases the flow of breast milk (Hussain and Hussain 2016). It contains more than 100 bioactive constituents of both herbal as well as industrial importance (Iqbal et al 2014). It is reported to be rich in essential fatty acids, sterols and higher concentration of thymoquinone (Piras et al 2013).…”
Section: Introductionmentioning
confidence: 99%